Peningkatan Pengetahuan dan Keterampilan Budidaya Ayam Petelur Melalui Pendampingan Edukasi untuk Siswa dan Mahasiswa di Desa Mendawai Kabupaten Kotawaringin Barat - Wulandari, Lies Tiarini; Hasanah, Laila Uswatun; Pratama, Rifki Tegar Adi (LPPM Universitas Palangka Raya, 2024)
Laying hens are used as an option in raising livestock because it is felt that the chicken can produce eggs in sufficient quantities in a fast time. The first egg is produced at the age of 6 months and will continue to produce eggs until it reaches 2 years old. With a total egg production between 250 to 280 eggs per year. Proper management in laying hens farming is crucial to achieve maximum production results. This community service activity is an educational mentoring program aimed at the younger generation to increase their knowledge and understanding of laying hen farming, starting from chick management, feed and drinking water management, housing, disease control, and egg handling. The activity took place at the Pialun poultry farm in Mendawai Village, West Kotawaringin Regency, with 7 participants. The implementation method began with a socialization session on laying hen farming in the first session, followed by the second session, which involved interviews with field assistants regarding management practices and skills in laying hen farming.